Food security assessment in Ukraine - Kundeyeva, Galina; Mostenska, Tetiana; Yevsieieva-Severyna, Iryna (My University, 2019)
The transformation of food security concept according to individual food preferences is considered. The issue of nutrition as a complex problem of rational balanced nutrition is distinguished. The importance of nutrition in the context of food security has been investigated. The relationship between the terms "food security" and "nutrition" has been analyzed. The concept of functional nutrition for the development of a new model of food production is investigated. Three aspects of nutrition research for the development of agricultural sector and food industry are highlighted. The analysis of nutrition, its caloric content and balanced diet by major macronutrients and micronutrients is conducted. Correlation between the level of nutrition and life expectancy of a person is determined. In international food safety research, the approach to the concept of food security is transformed according to individual food preferences. In the Rome Declaration on World Food Security (1996), food security implies not only the physical and economic accessibility of food in accordance with rational consumption norms, but also the food provision of the population due to their growing needs. This approach deals with the definition of food security, which was defined as physical and economic availability of food for any individual in accordance with his/her dietary needs and preferences, taking into account the peculiarities of nutrition.
Keywords: economic availabilit; food security; assessment; physical availability; кафедра економічної теорії